(untitled) - Peters, Michael H. (New York, 2007)
Real-Time Biomolecular Simulations provides you with proven strategies for shortening the time between product research, breakthrough, and introduction into the market. Based on the author's own innovative research, this rigorous, groundbreaking guide demonstrates how the simulation process can be accelerated yet still provide accurate, dependable results.
Keywords: Molecular dynamics,Biomolecules,Molecular biology,Macromolecules,Cell physiology,Hóa sinh học; Mathematical models.,Mathematical models.,Computer simulation,Technique.,Mathematical models.,Mathematical models.,Hóa sinh học di truyền